Konsep Al-Ma’rifah dalam Tradisi Sufisme Dzu al-Nun al-Mishri - Ma'rifat Iman (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2015)
In the world of Sufism, Dzu al-Nun al-Mishri is regarded as the father of al- ma’rifah. For him, al-ma’rifah is essential knowledge, by which some one is able to see God with the heart. Meanwhile, scientific knowledge cannot attain to the ulti- mate level. In order too reach the level of al-ma’rifah, someone has to pass asceticism by leaving behind the luxuries of life and always worshiping God . It is believed that when someone’s soul is clean of dirt, it is ready to accept al-faidh (abundance of God’s bless), or people can get to level al-ma’rifah by experiencing al-kasysyaf and ilham given by God. In sufism tradition, not everyone can reach the level of al- ma’rifah. A Sufi who has reached to the level of al-ma’rifah will have signs: 1) al- Ma’rifah always enlightening all his attitudes and actions; 2) He dos not make decisions based on real facts, because the concept of truth is Sufism is not based on real facts; 3) He does not show much expectation to God’s gift, because too much favors can laed to unlawful acts